Measuring nonlinear reflectance of laser radiation with a wavelength of from silica glass – water and silica glass – ethanol interfaces. (July 2016) - Gulyamova, E.S.; Il'ichev, N.N.; Pashinin, P.P.; Polyanskii, V.I.; Sidorin, A.V.
Abstract: We have measured the reflectance of an laser pulse from silica glass – water and silica glass – ethanol interfaces at high and low energy densities of incident radiation. The nonlinearity of reflectance dynamics is found for high-power radiation during the laser pulse action.